ANALYZING CULTURAL DISCOURSE IN JADID WRITINGS THROUGH CORPUS METHODS - Madina Dalieva (Bright Mind Publishing, 2025)
The Jadid movement in Central Asia, flourishing during the late 19th and early 20th centuries, sought to reform Muslim society through new educational methodologies, sociocultural modernity, and linguistic innovations. While scholarship on the Jadids has often focused on political and educational changes, relatively less attention has been paid to the cultural discourse embedded in their writings. This article examines cultural themes in Uzbek Jadid texts, drawing on corpus-based methods such as keyword analysis, collocation, and concordance. By analyzing references to family life, moral norms, and communal identity, we show how Jadid authors navigated tradition and modernity, advocating for both reform and continuity with Islamic-Turkic cultural roots. The findings underscore the importance of integrating computational text analysis with historical-linguistic approaches to reveal how reformist discourse shaped and reflected broader cultural values in early 20th-century Uzbekistan.
Keywords: Jadid movement; corpus linguistics; Uzbek; cultural discourse; digital humanities; collocation analysis.